Caesarean Section. Guideline of the DGGG, OEGGG and SGGG (S3-Level, AWMF Registry No. 015/084, June 2020) - Louwen, Frank; Wagner, Uwe; Abou-Dakn, Michael; Dötsch, Jörg; Lawrenz, Burkhard; Ehm, David; Surbek, Daniel; Essig, Andreas; Greening, Monika; Schäfers, Rainhild; Mattern, Elke; Waterstradt, Ina C.; Kästner, Ralph; Lütje, Wolf; Kranke, Peter; Messroghli, Leila; Wenk, Manuel; Kehl, Sven; Schlößer, Rolf; Lüdemann, Katharina; Maier, Barbara; Misselwitz, Björn; Heller, Günther; Bosch, Andrea; Nielsen, Renate; Rothe, Christiane; Sirsch, Erika; Kalberer, Barbara Stocker; Vogel, Thea; von Kaisenberg, Constantin; Nothacker, Monika; Hülsewiesche, Barbara; Allert, Roman; Jennewein, Lukas (Geburtshilfe und Frauenheilkunde, 2021)
Purpose This is an official S3-guideline of the German Society of Gynaecology and Obstetrics (DGGG), the Austrian Society of Gynaecology and Obstetrics (ÖGGG) and the Swiss Society of Gynaecology and Obstetrics (SGGG). The guideline contains evidence-based information and recommendations on indications, complications, methods and care associated with delivery by caesarean section for all medical specialties involved as well as for pregnant women.Methods This guideline has adapted information and recommendations issued in the NICE Caesarean Birth guideline. This guideline also considers additional issues prioritised by the Cochrane Institute and the Institute for Research in Operative Medicine (IFOM). The evaluation of evidence was based on the system developed by the Scottish Intercollegiate Guidelines Network (SIGN). A multi-part nominal group process moderated by the AWMF was used to compile this S3-level guideline.Recommendations Recommendations on consultations, indications and the process of performing a caesarean section as well as the care provided to the mother and neonate were drawn up.
Keywords: guideline; caesarean section